Erros em sistemas de leitura de tensiômetro em condições de temperatura controlada - Azevedo, Josimar de (2015)
Soil and water are essential resources for the development of agriculture. Thus, the knowledge on soil water dynamics is important for a good management of the resource water as a production factor. In this aspect, the following hypotheses were considered: 1) other tensiometer reading systems, specifically developed to measure soil water matric potential, substitute the mercury manometer with no loss of information quality; 2) when a digital tensimeter with pressure transducer is used in the tensiometer, given the disturbance caused by the insertion of the needle, a time interval is required for the reestablishment of the equilibrium between the tensions of the water inside the tensiometer and in the soil; and 3) even under controlled conditions, the reading systems for the measurement of soil water matric potential produce errors compared with the reference system, which affect the calculations that depend on this variable. This study aimed to evaluate two systems alternative to the mercury manometer for the quantification of the soil water matric potential, define the time necessary to reestablish the previously described equilibrium and quantify the errors involved. The experiment was performed using pots with mean diameter of 0.38 m and depth of 0.65 m, perforated at the bottom to allow drainage, reproducing the boundary conditions of the instantaneous profile method, with adaptations. The tensiometer reading systems were evaluated in the laboratory (21 ± 1 ºC); three tensiometers were installed in each pot at the depths of 0.20 m, 0.35 m and 0.50 m, totaling 18 devices, with 6 replicates. In order to avoid changes in the equilibrium between the air chamber, tensiometer water and soil water, the reading sequence was: mercury manometer, Bourdon gauge and digital tensimeter with pressure transducer (this one with readings at 30, 60, 90, 120, 150 and 180 seconds after needle insertion).At the end of the experiment, after 3052 h, it was concluded that: 1) after needle insertion of the tensimeter in the air chamber of the tensiometer, the reading must be performed in 30 seconds; 2) the tensimeter can substitute the standard system in the measurement of soil water matric potential in the moisture range from saturation until field capacity, and the Bourdon from a condition at or close to field capacity until a drier situation; and 3) the errors resulting from the use of systems alternative to the mercury manometer to obtain soil water matric potential also reflected in the measurement of soil moisture, and the alternative systems underestimated the values from the field capacity on